Manufacturing and potential applications of lattice structures in thermal systems: A comprehensive review of recent advances. (1st December 2022) - Sajjad, Uzair; Rehman, Tauseef-ur; Ali, Mubasher; Park, Cheol Woo; Yan, Wei-Mon
Highlights: Manufacturing and thermal applications of the lattice structure have been discussed in detail. Four classes of materials (polymers, ceramics, liquid resins and, metals and alloys) are considered for the detailed review. Pressure drop is not significant for lattice structure, unlike metallic foams. Thermo-hydraulic performance of the thermal systems is improved. Abstract: Lattice structures are a class of cellular materials with enhanced thermomechanical properties compared with their counterpart cellular materials such as foams. They have recently attracted researchers towards implementation in various engineering applications due to their diverse fabrication techniques driven by the advancement in additive manufacturing technology. This article reviews the four classes of materials (polymers, ceramics, liquid resins, and metals and alloys) used to fabricate the various lattice structures employed in different thermal applications. Firstly, the classification and description of the lattice structures are concluded, along with their applications in several domains in general and particularly in thermal systems. Secondly, the materials and fabrication techniques used for lattice structure manufacturing are briefly reviewed. Thirdly, extensive literature analysis is carried out on the heat transfer characteristics of numerous categories of lattice structures. Results revealed that lattice structures are the most promising media to enhance the thermo-hydraulic performance of heat-transferring systems in terms of augmenting the heat transfer rate and reducing the pressure drop. Meanwhile, some of its designs increase its thermal resistance, suitable for application in energy storage systems. On the basis of critical analysis of the fabrication, characterization and applications, several important conclusions are presented, along with the future research directions, to fill the gap in this area of research. Graphical abstract: Image, graphical abstract